(untitled) (Stato, Chiese e pluralismo confessionale, 2011)
This article is based on the lecture held on 23rd September 2011 at the Law faculty of the University of Bologna. SOMMARIO: 1. Introduction – 2. Statistical data – 3. The Muslim community – 4. The Jewish community – 5. General overview of the relevant law provisions in Bulgaria – 6. Anti-Semitism and Islamophobia and the political rights according to the domestic legislation – 7. The Law on Protection against Discrimination, the concept of “positive” discrimination and some new case-laws - 8. Religious Rights and Freedoms – 9. Criminal Law – 10. Some conclusions.